2010
DOI: 10.1021/es903891g
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Differential Biotransformation and Genotoxicity of ZnO and CeO2 Nanoparticles on Soybean (Glycine max) Plants

Abstract: Concern and interest related to the effects of nanomaterials on living organisms are growing in both the scientific and public communities. Reports have described the toxicity of nanoparticles (NPs) on micro and macro organisms, including some plant species. Nevertheless, to the authors' knowledge there are no reports on the biotransformation of NPs by edible terrestrial plants. Here, shown for the first time, is evidence pertaining to the biotransformation of ZnO and CeO 2 NPs in plant seedlings. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
289
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 549 publications
(320 citation statements)
references
References 31 publications
18
289
1
2
Order By: Relevance
“…We learned that these MNMs entered and accumulated in plants, and thus are bioavailable in this farm soil. Ce was mobilized from soil and accumulated into the roots with uptake levels similar to those observed in a hydroponic study (24). However, our results show that root nodules also acquire nano-CeO 2 , a finding only made possible from studying soilgrown plants.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…We learned that these MNMs entered and accumulated in plants, and thus are bioavailable in this farm soil. Ce was mobilized from soil and accumulated into the roots with uptake levels similar to those observed in a hydroponic study (24). However, our results show that root nodules also acquire nano-CeO 2 , a finding only made possible from studying soilgrown plants.…”
Section: Resultssupporting
confidence: 81%
“…Such Zn concentrations in various plant tissues were similar for equivalently dosed soybean (on a Zn mass basis) grown with Zn salts (33). However, nano-ZnO must have been highly bioavailable in this study soil, as Zn also substantially bioaccumulated in nano-ZnO-treated plants in a previous hydroponic study (24). Very high Zn accumulations could cause long-term impacts to either plant or human health (SI Appendix), but the extent and relationship to Zn form (including nano-ZnO) in the plant are unknown.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…By increasing the amount of ZnO NPs, the grain yield decreased by 42% (Table 5). According to the results of Lopez et al (2010), probably ZnO NPs reduced soybean (Glycine max) root growth and nutrient uptake and also as the result of leaves chlorosis, photosynthesis and plant growth reduced. John et al (2009) reported that the bud's growth reduction under Cu or Zn stress may result from the water potential reduction, hampered nutrient uptake and secondary stress such as oxidative stress, that eventually leads to decrease in yield and yield components.…”
Section: Yield and Harvest Indexmentioning
confidence: 99%